Interaction, language use, and second language teaching - Huth, Thorsten (New York, NY : Routledge, 2021)
This book presents a view of human language as social interaction, illustrating its implications for language learning and second language teaching. //The volume advocates for researchers, practitioners, and administrators to rethink and reconceptualize an understanding of language beyond that of the written word to one encompassing social and interactional activity built on co-construction, collaboration, and negotiation. The book emphasizes the ways in which this view of language can shed light on the language learning process as one which draws on discrete linguistic units and constructions in conjunction with a range of temporal, sequential, and embodied resources across a variety of social contexts. In turn, these insights prompt further reflection and discussion on their implications for advancing second language teaching practice. This book will be key reading for scholars interested in second language teaching research, as well as active second language teachers and language program administrators
Introduction -- Understanding interaction -- Understanding language learning -- Understanding interaction in the classroom -- Interaction, language use, and second language teaching
OCLC-licensed vendor bibliographic record.
Keywords: Language and languages -- Study and teaching; Second language acquisition; Social interaction; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics